2013
DOI: 10.1002/app.39661
|View full text |Cite
|
Sign up to set email alerts
|

Highly filled graphite polybenzoxazine composites for an application as bipolar plates in fuel cells

Abstract: Highly filled graphite polybenzoxazine composites as bipolar plate material for polymer electrolyte membrane fuel cell (PEMFC) are developed. At the maximum graphite content of 80 wt % (68 vol %), storage modulus was increased from 5.9 GPa of the neat polybenzoxazine matrix to 23 GPa in the composite. Glass transition temperatures (T g ) of the composites were ranging from 176 C to 195 C and the values substantially increased with increasing the graphite contents. Thermal conductivity as high as 10.2 W/ mK and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 27 publications
7
44
1
Order By: Relevance
“…Those values reduced from 336 J/g of the neat polybenzoxazine to 330 J/g of molding compound containing 10 wt% of graphene and to the value as low as 133 J/g of the molding compound containing 60 wt% of graphene. This expected phenomenon was related to the decreasing amount of benzoxazine resin in the molding compounds [10]. Figure 1b exhibited the DSC thermograms of graphene-filled benzoxazine molding compound at 10 wt% of graphene loading cured at 200 C at various curing time.…”
Section: Effects Of Graphene Loadings On Cure Behavior Of Benzoxazinementioning
confidence: 95%
See 3 more Smart Citations
“…Those values reduced from 336 J/g of the neat polybenzoxazine to 330 J/g of molding compound containing 10 wt% of graphene and to the value as low as 133 J/g of the molding compound containing 60 wt% of graphene. This expected phenomenon was related to the decreasing amount of benzoxazine resin in the molding compounds [10]. Figure 1b exhibited the DSC thermograms of graphene-filled benzoxazine molding compound at 10 wt% of graphene loading cured at 200 C at various curing time.…”
Section: Effects Of Graphene Loadings On Cure Behavior Of Benzoxazinementioning
confidence: 95%
“…Interestingly, the curing peak maximum of the molding compounds evidently shifted to lower temperature with higher amount of graphene loading. The positions of exothermic peaks of 10,20,30,40,50, and 60 wt% of graphene content in benzoxazine molding compound were 218, 212, 211, 209, 202, and 196 C, respectively. The results indicated that graphene might act as a catalyst for oxazine-ring opening reaction thus alleviated the curing condition in terms of energy consumption of the polymerization reaction.…”
Section: Effects Of Graphene Loadings On Cure Behavior Of Benzoxazinementioning
confidence: 99%
See 2 more Smart Citations
“…Machining is usually employed to fabricate the flow channels in the BPPs. Machining graphite into complex designs is highly expensive and time-consuming, and therefore makes it unpractical for the full scale commercialization of fuel cells [166,167].…”
Section: Bipolar Platesmentioning
confidence: 99%